نظام التكاليف الموجهة بالوقت كآلية للتحكم في التكاليف الخفية - نريمان بوعيطة (My University, 2021)
The purpose of the study that was carried out aims to provide a practical Framework for the implementation of the activity based costing system on time oriented activities in some institutions in light of the deficit of traditionel systems of costsby highlighting the role of accurate allocation of hidden costswherethis system wasused to determine these indirect costs ; so the study followed the descriptive approach to test hypotheses the study concluded with several results the most important of wichis the application of the time oriented costing system in instutitions. ................................................. تهدف الدراسة التي تم القيام بها إلى تقديم الإطار العملي لتطبيق نظام التكاليف على أساس الأنشطة الموجهة بالوقت في بعض المؤسسات في ظل عجز الأنظمة التقليدية للتكاليف من خلال إبراز دور التخصيص الدقيق للتكاليف الخفية حيث أستخدم هذا النظام لتحديد هذه التكاليف غير المباشرة، فاتبعت الدراسة المنهج الوصفي لاختبار الفرضيات حيث ختمت الدراسة بعدة نتائج أهمها نجاح تطبيق نظام التكاليف الموجهة بالوقت في المؤسسات.